Teacher’s pedagogical culture as an integral part of organizational culture development of teaching staff in vocational and technical institution - Polishchuk, T. P. (НТУ "ХПІ", 2015)
The approaches scientists to understand the essence of the organizational culture and its inseparability from pedagogical culture, has clarified the development of the organizational culture of the teaching staff of vocational education institution agrarian caused by the specific conditions of his life in the countryside.

В статті проаналізовано підходи науковців до розуміння суті організаційної культури, її невіддільність від педагогічної культури , з’ясовано особливості розвитку організаційної культури педагогічного колективу професійно-технічного навчального закладу аграрного профілю, що зумовлені специфічними умовами його життєдіяльності в сільській місцевості.
Педагогічна культура викладача – невід’ємна складова розвитку організаційної культури педагогічного колективу професійно-технічного навчального закладу
Keywords: pedagogical skills; teaching staff; vocational institution Agricultural Profile; organizational culture; педагогічна майстерність; педагогічний колектив; заклад аграрного профілю